The Effectiveness of Implementing the Shafi'i Method to Improve Quran Reading Skills for Women's Recitation groups - Alhamuddin; Heru Pratikno; Andi Murniati; Moh In’ami (Universitas Muhammadiyah Jember, 2023)
This research aims to improve the ability of the women's recitation group to read the Qur'an. The research uses qualitative approach and experimental method. Practices and tests. The data were analyzed using descriptive statistics. The results showed that: (a) The lack of participants in the ability to read the Qur'an due to the lack of innovation in Qur'anic learning carried out by the teacher, as well as the lack of infrastructure that supports the development of Qur'anic learning in the mosque (b) The effectiveness of Qur'anic learning through the use of methods is very influential on the development of Qur'anic reading skills of participants. As a result of this activity, the Qur'an reading ability of the congregation of the teaching assembly has increased. As a suggestion, similar activities need to be carried out on an ongoing basis. This will help to maintain and sustain the results achieved.